PELATIHAN SENI MERANGKAI BUNGA JEPANG(IKEBANA) DI PANTI LANJUT USIA WENING WARDHOYO UNGARAN - Reny Wiyatasari (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
This service’s activity to society aims to find out introduce the art of Japanese flower arrangement (ikebana)and how to make ikebana to the mothers of nursing homes for Wening Wardhoyo. Through this activity, it is expected that nursing home residents Wening Wardhoyo can find out the types of ikebana and how to make them. This service’s activity to societyactivities in the form of training were attended by around 35 participants. The following is the sequence of activities: 1) dividing participants into groups and accompanied by a companion; 2) see a video that shows how to make the Ikebana; 3) distributing flowers, materials and equipment needed; and 4) The companion starts the activity by soaking the oasis as a medium to plant flowers. Then cut flowers at the request of participants; 5) The flowers that have been cut, are then assembled and plugged in by the participants alternately and the participants create according to their own desires. From this activity nursing home residents have activities in their spare time and training activities to make ikebana will grow new memories in their old age. Moreover, the participants could feel happy because even though they were in a nursing home in their old age there were still people who loved and cared for their existence.Keywords:ikebana, nursing home, wening wardhoyo, oasis